(3QSGdI JbdjO GdoeLJHj JbdjOkG CVefs ((3MeRI Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3CYde habc Gdehdi hefMc SHd GdgOi hCYGPc ef GdZj hGdghi HeG oJMH hJQVi s
(3BNQgG (B:s
(3hHg CSJYjf hfYe GdfUjQ GdoeYjf oSHMGfg hMOg dGTQjc dg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3QSGdI ef QSGFd GdOQhRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds